LAURA MILLAR, The Story Behind the Book: Preserving Authors’ and Publishers’ Archives - Wyckoff, Wade (Archivaria, 2014)
The Story Behind the Book: Preserving Authors’ and Publishers’ Archives. LAURA MILLAR. Vancouver: Canadian Centre for Studies in Publishing, 2009. 224 pp. ISBN 978-0-9738727-4-3.